Semiconductor Quantum Dots: Synthesis, Properties and Applications - Donghai Feng; Guofeng Zhang; Yang Li (Nanomaterials)
Semiconductor nanoparticles of sizes smaller than exciton Bohr diameters undergo quantum confinement and are called quantum dots (QDs), which exhibit size-dependent physicochemical properties [...]